Rose - Webb, Holly (London Orchard Books, 2009)
Adopted from the dark orphanage of her childhood and brought to the grand residence of the famous alchemist Mr. Fountain, Rose finds the house overflowing with sparkling magic and wonders if she has magic inside her, too.
Keywords: Orphans -- Magic -- Alchemy